A case-control study on alcohol and psychiatric disorders as risk factors for drug abuse pattern - Claudia S. Lopes; Rosely Sichieri
We evaluated alcohol and psychiatric disorders as risk factors for the pattern of drug abuse/dependence in a matched case-control study (370 adults). Cases (drug abusers) and controls were selected in the community using the snowball technique and matched by sex, age, and friendship. Information was gathered using the "Composite International Diagnostic Interview" (CIDI). Three patterns of drug abuse/dependence were evaluated: any drug abuse/dependence, only cannabis, and cocaine and other drugs. Logistic conditional regression showed that alcohol dependence was strongly associated with pattern of drug abuse/dependence. Thus, compared to the "no drug abuse group", the odds ratio for association with diagnosis of abuse/dependence on cocaine and other drugs was 10.2 (95% CI: 4.9-21.2), whereas for abuse/dependence on cannabis only, the odds ratio was 1.0. For affective disorders, the odds ratio was 2.0 (95% CI: 1.10-3.64) for the group that received a diagnosis of abuse/dependence on cocaine and other drugs, whereas no association was found for those with abuse/dependence on cannabis only. In conclusion, there is not a homogeneous group of "drug users", and the role of risk factors depends on the drug use pattern.